Acid-sensing ion channel 1a-mediated calcium influx regulates apoptosis of endplate chondrocytes in intervertebral discs. (January 2014) - Li, Xia; Wu, Fan Rong; Xu, Rui Sheng; Hu, Wei; Jiang, Dong Lin; Ji, Cheng; Chen, Fei Hu; Yuan, Feng Lai
<x xml:space="preserve">Abstract</x> Background: Acid-sensing ion channel 1a (ASIC1a), the primary acid sensors in the nervous system, has been studied earlier in various physiopathologic conditions. However, little is known about the role of ASIC1a in endplate chondrocytes in intervertebral discs (IVDs). Methods: The expression of ASICs was examined in rat endplate chondrocytes. Effects of treatment with ASIC1a small interfering RNA (siRNA) or selective blocker (PcTX1) on acid-induced intracellular Ca2+ concentration ([Ca2+]i) and cell apoptosis were investigated. ASIC1a involved in Ca2+-mediated apoptotic signals in acid-induced endplate chondrocyte apoptosis was also assessed. Results: We showed that ASIC1a is expressed in rat endplate chondrocytes, and blockade of ASIC1a using ASIC1a-siRNA or PcTX1 inhibited acid-induced cell apoptosis and elevation of [Ca2+]i. We also demonstrated that the acid-induced [Ca2+]i increase via ASIC1a is involved in endplate chondrocyte apoptosis. Moreover, blocking of ASIC1a-mediated [Ca2+]i elevation inhibited activation of acid-induced calcium-dependent proteases and decreased BAD phosphorylation in endplate chondrocytes. Similarly, extracellular acidosis induced cytochrome C translocation from the mitochondria to the cytoplasm and activation of caspase-9 and caspase-3, which was inhibited by ASIC1a-siRNA or PcTX1. Conclusion: ASIC1a activation in endplate chondrocytes may trigger Ca2+-dependent proteases activity and signaling, which leads to apoptosis of endplate chondrocytes in IVDs.